PENGARUH PERSEPSI ATAS LINGKUNGAN SEKOLAH DAN MOTIVASI BELAJAR TERHADAP PRESTASI BELAJAR ILMU PENGETAHUAN SOSIAL - Nur Azizah (Universitas Indraprasta PGRI, Jakarta, Indonesia, 2018)
Based on the results of this study concluded that: 1) There is a significant influence on the Perception of the School environment and student Motivation together with student achievement Privat Vocational School Sciens in West Jakarta. This is evidenced by the value Sig = 0.004 and the value of F = 6,207. 2) There is a significant influence on the Perception of the School environment on student achievement Privat Vocational School Sciens in West Jakarta. This is evidenced by the value Sig = 0.032 and tcount = 2.193. 3) There is a significant effect of learning Motivation on student achievement Privat Vocational School Sciens in West Jakarta. This is evidenced by the value Sig = 0.041 and tcount = 2.093